The origins of the legislative drafting of the penal procedure rule - حسين كاظم عبد الله; اسماعيل شاكر نوري (Journal of Legal Sciences, 2019)
The legal structure of the criminal procedural rules consists of two elements: the first is substance or substance and is the primary material of those rules. It is the values ​​which the legislator aims to protect in order to achieve the desired interest. This can only be done by putting that content or substance into molds that can be applied By legislative drafting of legal rules and this second element, in which the legal construction of legal norms is completed and the final form of the legal rules becomes applicable and the legislative formulation conveys the essence of the rule of law From the static theory to the practical situation. and for the purpose of achieving the purpose for which the legal basis was found to be followed the principles of the legislative drafting of the legal rules and according to the procedural criminal policy followed by the legislator, as the legislative wording varies according to the authority or right granted by the legislator to the perpetrators of the rule of criminal procedure , The wording of the legislative form is divided in terms of style into rigid formulation and flexible formulation, and the method used in drafting may be material or moral. Therefore, we discussed the origins of the legislative drafting in the procedural rules in the Iraqi Code of Criminal Procedure, with some shortcomings in the formulation of its rules, and it was found that the Iraqi legislator has taken various legislative drafting methods.